PENGARUH PEMBERIAN KREDIT GADAI KCA TERHADAP PENDAPATAN SEWA MODAL DI PT PEGADAIAN CABANG WOLOWONA KABUPATEN ENDE - Fedo, Ermelinda; Djou, Laurentius D Gadi; Kapa, Sesilianus (Jurnal Riset Ilmu Akuntansi, 2021)
The problems that occur are what is the level of KCA pawning credit, how is the level of capital lease income and how much influence does KCA pawning credit give to capital lease income at PT Pegadaian, Wolowona branch. This study aims to determine the level of KCA pawning credit at PT Pegadaian, Wolowona branch, the level of capital rental income at PT Pegadaian, Wolowona branch, and the effect of KCA pawning credit on rental income at PT Pegadaian, Wolowona branch. The method in this study uses simple linear regression analysis, t test, and the coefficient of reduction to determine the effect of KCA pawning credit on capital rental income at PT Pegadaian, Wolowona branch, Ende district. The data sources are primary data and secondary data. Data collection techniques in this study were observation, interviews, and documentation. Based on the test results using simple linear analysis, t test, and determinant coefficient, it shows that the provision of mortgage loans has a significant effect on capital rental income at PT Pegadaian, Wolowona branch, Ende district.